Sunscreen lip balm stick formulation containing a combination of virgin coconut oil and crude palm oil - Nareswari, Tantri Liris; Syafitri, Erga; Nurjannah, Okta (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2022)
Virgin coconut oil (VCO) and crude palm oil (CPO) are products of Indonesia’s natural wealth with significant antioxidant activity and potential as lip balm sticks to treat dry lips caused by sun exposure. This study aims to determine the formulation of lip balm stick preparations containing VCO and CPO that have sunscreen activity and acceptable physical characteristics. This study included the phases of testing, formulation of lip balm stick, sunscreen activity test, and evaluation of physical properties. The compositions were melted using a water bath, and the sunscreen’s efficacy was evaluated using UV-Vis spectrophotometry. VCO and CPO concentrations varied between 5%, 7.5%, 10%, 12.5%, and 15% (w/w). The F1 formula containing 5% VCO and 15% CPO (w/w) had the highest sun protection factor (SPF) value of 15.438. The evaluation of the formula activity test revealed that the higher the CPO content, the greater the sunscreen activity. Formula F1 has stable physical properties while stored at room temperature for 28 days. Formula F1 has a yellow color, chocolate scent, semi-solid consistency, homogeneous, 3.35 cm dispersion, 56 oC melting point, and 64-gram hardness. Formula F1 provides excellent sun protection and physical properties. It may be further evaluated as a lip balm stick sunscreen formulation for chapped lips.